Adipsin a regulatory protein found in the extracellular matrix is modulated by hypercholesterolemia in myocardial infarction. (10th June 2022) - Padro, T; Garcia-Arguinzonis, M; Vilahur, G; Diaz-Riera, E; Badimon, L
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Agencia Estatal de Investigación (AEI)- Spanish Institute of Health Carlos III, ISCIII; Agencia Estatal de Investigación (AEI)- Spanish Ministry of Economy Competitiveness of Science Background: Local inflammation and innate immunity are key features during cardiac remodelling post myocardial infarction (MI). Adipsin, a component of the inflammatory response, is the major activator of the C3-complement pathway and exerts elastolytic activity. Beyond liver, adipsin is mostly secreted from adipocytes, monocytes and macrophages. It is to notice that intramyocardial lipid accumulation alters the fibrotic reparative process of the scar, resulting in larger infarcts and cardiac dysfunction in a pig model. Adipsin could directly contribute to collagen turnover in the cardiac extracellular matrix (ECM) during formation of the post-MI scar. Purpose: The role of adipsin in the setting of myocardial infarction remains unknown. Here we investigated adipsin changes (content and activity) in the cardiac ECM of MI pigs and determine whether hypercholesterolemia relates to the turnover of the ECM-collagen pattern in association with the adipsin content. Methods: Normo- (NC) and diet-induced hyper- (HC) cholesterolemic animals (N=28) were randomly distributed to MI-induction or sham-operation (N=7 animals/group). MI was induced by 90min closed-chest coronary balloon occlusion. After revascularization, animals were either maintained for 2.5hours or 30days before being sacrificed.  Adipsin, C3- activation products (as readout of adipsin activity) and collagen fragmentation products were determined in cardiac ECM-extracts from the ischemic and non-ischemic regions in all pigs. Results: Adipsin and C3-activation products (iC3b, C3dg) were consistently detected in the cardiac ECM of sham-operated animals. Detection levels of adipsin, iC3b and C3dg were >2fold higher in HC vs NC pigs (p<0.05) suggesting higher adipsin activity in hearts of animals with high cholesterol levels. NC and HC MI-pigs subjected to 2.5hours reperfusion showed an acute and sharp increase in cardiac adipsin detection in the ischemic region as compared to sham and non-ischemic areas (p<0.05).  At 30days post-MI, adipsin content in the scar was comparable to that of sham-operated animals remaining significantly higher in HC vs NC pigs. Yet, adipsin cardiac levels in the scar of HC animals were associated with a lower content of fibrillar collagen-1 (MW: 235kDa) and a higher proportion of proteolytic collagen-fragments (MW: 135-48 kDa) (p<0.05 vs NC pigs) Conclusions: Adipsin is a component of the cardiac ECM. Hypercholesterolemia enhances myocardial adipsin content and activity and promotes proteolysis of collagen fibrils in the forming scar contributing to the cardiac remodeling during post-infarction.